(3GdeSGdc hGdeeGdcs - (3YHO Gddg Hf YHO GdYRjR Hf eMeO GdHcQj GdCfOdSj, CHh YHjO,J (B487 (3g` s
(3ChdgG (B:s
(3GdeSGaGJ Hjf JSYI aQGSN s
(3BNQgG (B:s
(3hgj cGfJ bGYOI Hjf hgj ai SaM LHd hdgG KeGQ hejGg cKjQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B75s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1664s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs